2006
DOI: 10.1111/j.0730-7659.2006.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parity on Course of Labor in a Contemporary Population

Abstract: Additional childbearing appears to have no effect of on the progression of labor among multiparous subgroups. The difference in duration of the active phase between nulliparas and multiparas is substantially smaller in a contemporary population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
1
42
0
1
Order By: Relevance
“…The different findings in these studies may be attributable to different populations studied and the different labor management protocols used. One study examined progress of labor in nulliparous women undergoing induction, stratified by favorability of the cervix at the time of induction 15 . Similar to our results, they found that progress in one centimeter increments from 3 to 6 cm was slower with the Foley catheter compared to spontaneous labor, but labor patterns were similar thereafter.…”
Section: Commentmentioning
confidence: 99%
“…The different findings in these studies may be attributable to different populations studied and the different labor management protocols used. One study examined progress of labor in nulliparous women undergoing induction, stratified by favorability of the cervix at the time of induction 15 . Similar to our results, they found that progress in one centimeter increments from 3 to 6 cm was slower with the Foley catheter compared to spontaneous labor, but labor patterns were similar thereafter.…”
Section: Commentmentioning
confidence: 99%
“…Compared to multiparous women, primiparas have longer labours [13], are at an increased risk of intrapartum complications [4–7] and undergo substantially more obstetric interventions [8–11]. The use of interventions, especially assisted vaginal delivery and unplanned caesarean delivery, has been found to have a negative impact on women’s birth experience, which may partly explain why primiparous birth experiences are more negative [1214].…”
Section: Introductionmentioning
confidence: 99%
“…12,20 When cervical dilatation occurs rapidly, a short duration of labor could explain the low analgesic effectiveness of the epidural technique. 21 We found that nationality was not associated with epidural analgesia effectiveness. Besides, a recent single-center prospective observational study reported that ethnicity plays at most a small role in the acceptance of and requests for neuraxial analgesia.…”
Section: Discussionmentioning
confidence: 64%